A Non-Woven Network of Porous Nitrogen-doping Carbon Nanofibers as a Binder-free Electrode for Supercapacitors. (10th March 2017) - Li, Xinlu; Zhao, Yujie; Bai, Yu; Zhao, Xiyu; Wang, Ronghua; Huang, Yanchun; Liang, Qinghua; Huang, Zhenghong
Abstract: A non-woven network of porous nitrogen-doping carbon nanofibers (PNCNFs) is prepared by electrospinning of polyacrylonitrile (PAN)/polyvinylpyrrolidone (PVP), followed by stabilization and carbonization. The specific surface areas, porosity and nitrogen content of PNCNFs can be easily controlled by adjusting the content ratio of PVP to PAN. The non-woven PNCNFs based network provides abundant interface sites and hierarchical porosity for solvated ions. In a three-electrode configuration, PNCNFs-2-3 provides a high specific capacitance of 198 F g −1 at 1 A g −1 in 6 M KOH. A two-electrode configuration supercapacitor using PNCNFs-2-3 delivers 148 F g −1 capacitance at 1 A g −1 as well as excellent cycling stability.